Komunikasi Promosi Word to Mouth Warung Kopi di Kota Padang (Studi Kasus pada Warung Kopi Tradisional dan Warung Kopi Modern) - Pratiwi Rahmadani; Elva Ronaning Roem; Sarmiati Sarmiati (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study aims to explain the marketing communications of coffee shops in the city of Padang through a study of traditional and modern coffee shops. This study uses qualitative research methods and types of case study research and analyzes them using the Elaboration Likelihood Theory. The results of the first study show that marketing communications through Word of Mouth in coffee shops play a very large role in coffee sales. This Word of Mouth promotion is marked by people who have subscribed and will invite their family or friends to enjoy coffee at the shop. The impact of this Word of Mouth promotion is marked by the enthusiasm of customers visiting coffee shops, the use of working space as an effort to promote modern coffee shops, the use of coffee shops as public spaces, and the absence of gaps between women and men. Second, efforts to maintain the existence of coffee shops in the city of Padang can be seen in the characteristics of coffee shops that adapt to contemporary concepts, are able to establish interactions with customers, and actively carry out product innovations.